PERAN PENDIDIKAN SOSIAL BUDAYA TERHADAP PEMBENTUKAN KARAKTER PEDULI LINGKUNGAN PADA MASYARAKAT DESA PANGLIPURAN - Fitriyadi Ningsih, Ajeng; Azkiyatun Salsabila, Nur; Syahrial, Alvi; Setiyoko, Didik Tri; mulazamah, elok (ADIDAYA : Aplikasi Pendidikan dan Sosial Budaya, 2025)
This study was conducted to determine the role of socio-cultural education in Penglipuran village, which is related to the formation of the character of the village community. This study shows how important socio-cultural education is for the people of Penglipuran. Starting with the study of information from the research subjects, namely one of the village residents and the travel guide. Based on interviews and observations conducted, the results of the progress of Bali's cleanest villages are not only based on education, but also because of the traditions, culture and customs that are still nearby. This is because Bali still has a fat concept of life and habits. All actions that a person thinks about himself if not done according to habit.